Origin of Lower Cretaceous quartzose arenites in northern India and the Indus Basins of Pakistan—The result of provenance composition, weathering or diagenesis?. (5th October 2022) - Beaumont, Hazel; Burley, Stuart D.; Breitfeld, Tim; Gould, Thomas; Clarke, Stuart M.
Abstract: Lower Cretaceous (Aptian‐Albian) sandstones of the Ghaggar‐Hakra Formation in the Barmer Basin of northwest Rajasthan, India, have a complex depositional history which is confusing given they are quartzose arenites. The heavy mineral grains are very well‐rounded, and the assemblage is dominated by zircon and rutile grains suggesting that the sediments have been recycled multiple times, whilst the presence of staurolite indicates a metapelite provenance component. Petrographical analysis suggests that extreme diagenesis cannot account for the quartzose arenite composition, despite Early Cretaceous soil formation and at least two periods of subsequent telogenetic modification. An alternative explanation to extreme chemical weathering in the provenance area is that the Ghaggar‐Hakra sandstones are multi‐cycle sediments derived, at least in part, from the quartzose arenites of the Cambrian Jodhpur Group. This analysis suggests that variations in detrital mineralogy across the Western India Rift System and Indus Basins are the result of transcontinental fluvial transport systems sourcing sediment from specific basement highs (Nagar Parker High, Devikot High, Deodar Ridge and Aravalli Mountain Range) mixed with varying proportions of sediment derived from sandstones of the Jodhpur Group. Consequently, we suggest that Cretaceous fluvial systems were controlled by the local palaeogeographies within the failed rifts of the Barmer and Cambay Basins and that both basins formed barriers to sediment transport from the Aravalli Mountain Range across the northwest Indian plate and into surrounding basins. Abstract : Palaeogeographical reconstruction displaying the provenance terrains exposed across the northern Indian Plate in the Lower Cretaceous Epoch able to provide sediment detritus delivered to the Barmer and Cambay basins. Variations in detrital mineralogy across the WIRS and LMIB result from fluvial transport systems sourced from multiple highs and controlled by the rift palaeogeographies. It's like the failed rifts of the Barmer and Cambay basins form a natural transport barrier that precluded the transport of detritus from the Aravalli Mountain Range across these deep rifts into the more westerly rift basins of the Kachchh and South Indus basins.